In Vivo Phosphoproteome Analysis Reveals Kinome Reprogramming in Hepatocellular Carcinoma - Ren, Liangliang (Mol Cell Proteomics, 2018)
Aberrant kinases contribute to cancer survival and proliferation. Here, we quantitatively characterized phosphoproteomic changes in an HBx-transgenic mouse model of hepatocellular carcinoma (HCC) using high-resolution mass spectrometry, profiled 22,539 phosphorylation sites on 5431 proteins. Using a strategy to interpret kinase- substrate relations in HCC and to uncover predominant kinases in tumors, our results, revealed elevated kinase activities of Src family kinases (SFKs), PKCs, MAPKs, and ROCK2 in HCC, representatives of which were further validated in cell models and clinical HBV-positive HCC samples. Inhibitor combinations targeting Src and PKCs or ROCK2 both synergized significantly to inhibit cell growth. In addition, we demonstrated that phosphorylation at Src Ser17 directly affects its kinase activity. Our phosphoproteome data facilitated the construction of a detailed molecular landscape in HCC and should serve as a resource for the cancer community. Our strategy is generally applicable to targeted therapeutics, also highlights potential mechanisms of kinase regulation.